2019
DOI: 10.3390/cells8101119
|View full text |Cite
|
Sign up to set email alerts
|

Serine Protease HtrA2/Omi Deficiency Impairs Mitochondrial Homeostasis and Promotes Hepatic Fibrogenesis via Activation of Hepatic Stellate Cells

Abstract: The loss of mitochondrial function impairs intracellular energy production and potentially results in chronic liver disease. Increasing evidence suggests that mitochondrial dysfunction in hepatocytes contributes to the activation of hepatic stellate cells (HSCs), thereby resulting in hepatic fibrogenesis. High-temperature requirement protein A2 (HtrA2/Omi), a mitochondrial serine protease with various functions, is responsible for quality control in mitochondrial homeostasis. However, little information is ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…HTRA2 is an integral member of the HTRA family of serine proteases, which plays an essential role in mitochondrial homeostasis and cell apoptosis (Toyama et al, 2021; Wang & Nie, 2021; Zheng et al, 2021). Hur et al (2019) found that HTRA2 deficiency impaired mitochondrial homeostasis and promoted hepatic fibrogenesis. However, no direct evidence has shown that HTRA2 serves as a regulator in the progression of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…HTRA2 is an integral member of the HTRA family of serine proteases, which plays an essential role in mitochondrial homeostasis and cell apoptosis (Toyama et al, 2021; Wang & Nie, 2021; Zheng et al, 2021). Hur et al (2019) found that HTRA2 deficiency impaired mitochondrial homeostasis and promoted hepatic fibrogenesis. However, no direct evidence has shown that HTRA2 serves as a regulator in the progression of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that mitochondrial dysfunction plays a key role in activated HSCs, although the mechanisms underlying this dysfunction are still unclear. 36 , 37 , 38 The main function of mitochondria is to carry out oxidative phosphorylation (OXPHOS) to synthesize ATP, and mitochondria are the site of the final oxidation of sugars, fats and amino acids to release energy. 39 Therefore, we first analyzed mitochondrial function by changing PLIN 5 expression in in vitro‐cultured rHSC‐primary cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial copy numbers were measured using absolute RT-qPCR, as previously described [ 59 ]. Briefly, genomic DNA from C2C12 myoblasts was isolated using the DNeasy Blood and Tissue Kit (QIAGEN, Hilden, Germany) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%